2000
DOI: 10.1103/physrevlett.84.4397
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microscopic Mechanism of Intermixing during Growth on Soft Metallic Substrates

Abstract: Generic computer simulations using empiric interatomic potentials suggest a new, collective mechanism that could be responsible for mixing at heteroepitaxial interfaces. Even if single adsorbate atoms diffuse by hopping on the substrate surface and do not mix at the terraces, two-dimensional islands formed by nucleation may become unstable above a certain critical size and explode upwards forming clusters of several atomic layers. This process is accompanied by strong distortions of the underlying atomic layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
5
37
0
1
Order By: Relevance
“…Multiple height island formation, step decoration, vacancy (pools) islands and Cu-Co intermixing are common features in this system [9,10]. In a recent work, we showed that this behavior depends on the adsorbate -substrate interaction, and it should be awaited any time materials of these types are put into contact [11].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple height island formation, step decoration, vacancy (pools) islands and Cu-Co intermixing are common features in this system [9,10]. In a recent work, we showed that this behavior depends on the adsorbate -substrate interaction, and it should be awaited any time materials of these types are put into contact [11].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier theoretical study by Gomez et al [10] using Monte Carlo and static relaxation provides a second interesting comparison of Co growth on Cu(111). In part, this study looked at preferential nucleation sites of Co at Cu steps and drew the following conclusions: (1) Co atoms will form "two nearly straight rows", one in front of the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, despite extensive prior work in the Co/Cu materials systems, no atomic wires of Co on Cu(111) surfaces were observed experimentally, although the existence of Co wires at Cu step edges was predicted theoretically [10,11]. Note, however, that there are several reports of the direct observation of atomic wires in different bi-metallic systems, e.g.…”
Section: Co Nucleation On Cu(111) Steps: Prior Experimental Workmentioning
confidence: 92%
See 1 more Smart Citation
“…STM experiments [7] also suggest that the islands include a subsurface Co layer. In addition, theoretical calculations using empirical interatomic potentials indicate that two-dimensional Co islands become unstable above a certain critical size and "explode" upwards, dragging Cu atoms from the surface layer forming mixed- composition islands several layers high [8].…”
Section: Resultsmentioning
confidence: 99%